Incidence and characteristics of cesarean deliveries in a public hospital in Paraguay - Franco Netto, Raphael Oliveira Ramos (2023)
Objective: To verify the incidence of caesarean and vaginal delivery in women treated in a public hospital in the city of Pedro Juan Caballero - Paraguay and to know the most frequent indications for caesarean operations. Material and methods: The study was descriptive, retrospective, and documentary, based on information from medical records. The data collection place was the Pedro Juan Caballero Regional Hospital, Paraguay. The population chosen for the study consisted of pregnant women from 14 years of age, in the period from June 2018 to June 2019, totaling 2,087 records. 2087 records were analyzed, of which 200 deliveries by caesarean section were selected 200 records of deliveries by caesarean section performed in this period (26.28% of the total). Results: 761 cesarean sections were registered, corresponding to 36.28% of deliveries and 1,326 vaginal deliveries. Cesarean section was more prevalent among women between 24-27 years of age, representing 24% of the total. Among the indications for caesarean section, it was observed that 16.5% were for a previous caesarean section, 11% for preeclampsia, 10.5% placental abruption, 10% for fetal bradycardia, and 8.5% for breech presentation, all These indications represented 56% of the total number of cesarean deliveries evaluated. Conclusion: The cesarean delivery rate was high in the investigated Hospital (36.28%), when the WHO established a desired rate of up to 15%. The most frequent indications found in this study were Cesarean section, Preeclampsia, Placental abruption, and Fetal bradycardia.